Choral Conducting Competence as a Pedagogical System - Savchenko, Regina; Savchenko, Yulia (Journal of History Culture and Art Research, 2019)
This article discusses the essence and structure of the choral-conductor competence of students of higher educational institutions of musical-pedagogical profile. The criteria for the quality of student preparation for the effective implementation of his/her practical activities are indicated. The purpose of the article is to substantiate the practical need for the formation of a choral-conductor competence of a future musician teacher. To achieve this goal, the following tasks were set: to consider the conducting and choral competence as a pedagogical system; to highlight the knowledge, skills, abilities, and personality traits necessary in mastering the conducting profession; to identify ways to enhance the needs of the choirmaster conductor in creative activities in working with the team; to reveal and analyze certain aspects and components of the professional training of choirmaster conductors in social relations, to find a dynamic view of a person’s future, new dimensions of his/her self-realization; substantiate conclusions and promising areas for further consideration of the chosen problem. The main methods used in the study are comparative, analytical, systemic, and structural. Conclusions: The notions about the possibilities of conducting choir training in musical and pedagogical training of students are expanded: awareness of its potential in the educational process; consideration of the choral-conductor competence of future specialists as an integral system of musical and pedagogical education. On the basis of scientific research, new guidelines in the preparation of a competent specialist were identified, the concept of “choral-conductor competence” was specified, indicators of the specifics of its activity were determined, and the potential of its professional capabilities was identified. The solution to this problem depends on the choral-conductor installation of the future specialist, that is, his/her readiness to organize and manage the process of collective performance of a vocal-choral work.